A Girl's A Gun : Poems - Peterson, Rachel Danielle (Book collections on Project MUSE., 2017)
Haunting and candid, A Girl's A Gun introduces a poet whose bold voice merges heightened lyricism with compelling narrative. Steeped in storytelling traditions, the poems in Rachel Danielle Peterson's debut collection exhibit linguistic dexterity and mastery of form as the poet mixes lyrical paragraphs, sonnets, and interview-style poems with free verse. Hey Yvonne! The memoree of some strangerhis shoulder's shadow plunges inta our place: thunk, thunk. Run! Mother's vowels pierce haze. Mother, can we distil the pink threads, fabric, black ball cap, the odor of Bud Light, fills the door she walks through, dust, Mamma. Dust is all we isTaken together, the poems present the coming-of-age story of a girl born in the mountains of rural eastern Kentucky, tracing her journey into a wider world of experience. While the early poems are steeped in Appalachian speech and culture -- a hybrid of a child's diction and regional dialect -- the language shifts as the collection progresses, becoming more standard. The speaker engages with hard issues surrounding gender and violence in contemporary life and explores what it means to be an artist in a culture that favors a literal interpretation of reality. Exploring issues of identity, place, and the call to create, this collection tackles subjects that will shock, touch, and bewilder readers while giving voice to an underrepresented and perhaps even unprecedented perspective in poetry.